Correlation between maximum isometric strength variables and specific performance of Brazilian military judokas - Michel Moraes Gonçalves; Claudio Joaquim Borba-Pinheiro; Runer Augusto Marson; Lucas Rodrigues Camposo; Alam dos Reis Saraiva; Jefferson da Silva Novaes (Desafio Singular, 2017)
It was our objective to correlate specific performance in the Special Judo Fitness Test (SJFT) and the maximum isometric handgrip (HGSMax), scapular traction (STSMax) and lumbar traction (LTSMax) strength tests in military judo athletes. Twenty-two military athletes from the judo team of the Brazilian Navy Almirante Alexandrino Instruction Centre, with average age of 26.14 ± 3.31 years old, and average body mass of 83.23 ± 14.14 kg participated in the study. Electronic dynamometry tests for HGSMax, STSMax and LTSMax were conducted. Then, after approximately 1 hour-interval, the SJFT protocol was applied. All variables were adjusted to the body mass of the athletes. Pearson correlation coefficient for statistical analysis was used. The results showed moderate negative correlation between the SJFT index and STSMax (r= -0.550, p= 0.008), strong negative correlations between the SJFT index and HGSMax (r= -0.706, p< 0.001), SJFT index and LTSMax (r= -0.721; p= 0.001), besides the correlation between the sum of the three maximum isometric strength tests and the SJFT index (r= -0.786, p< 0.001). This study concludes that negative correlations occur between the SJFT index and maximum isometric handgrip, shoulder and lumbar traction strength and the sum of the three maximum isometric strength tests in military judokas.